POLA KOMUNIKASI SOSIAL DALAM PELESTARIAN BUDAYA JEG-AJEGEN: STUDI KASUS GOTONG ROYONG MASYARAKAT DESA SUMBERANYAR SITUBONDO - Ahmad Saleh; A.Khairudin (Maddah : Jurnal Komunikasi dan Konseling Islam, 2026)
This study aims to analyze the patterns and systems of social communication within the "Jeg-Ajegen" mutual assistance (gotong royong) tradition in Sumberanyar Village, Banyuputih District, Situbondo Regency. "Jeg-Ajegen" is a local wisdom of the Madurese-speaking community which literally means "inviting one another" to assist others without expecting financial compensation. This research employed a qualitative method with a case study approach. Data were collected through in-depth interviews with community leaders and local residents, field observations, and documentation. The results indicate that the sustainability of the "Jeg-Ajegen" tradition is supported by three main communication system patterns: (1) Linear Communication, which is one-way communication via mosque or mushalla loudspeakers for collective activities such as cleaning drainage channels; (2) Interactional Communication, which is two-way face-to-face communication carried out by directly visiting neighbors' homes to request assistance for family events or house renovations; and (3) Transactional Communication, which represents multi-party collaboration involving role exchange between residents and village government officials in providing logistics and labor for public facility projects. These findings suggest that adaptive and emotionally nuanced interpersonal communication patterns effectively preserve social harmony, solidarity, and rural cultural integrity amid the wave of modernization.